Differential cell death decisions in the testis: evidence for an exclusive window of ferroptosis in round spermatids. (13th March 2019) - Bromfield, Elizabeth G; Walters, Jessica L H; Cafe, Shenae L; Bernstein, Ilana R; Stanger, Simone J; Anderson, Amanda L; Aitken, R John; McLaughlin, Eileen A; Dun, Matthew D; Gadella, Barend M; Nixon, Brett
Abstract: Oxidative stress is a major aetiology in many pathologies, including that of male infertility. Recent evidence in somatic cells has linked oxidative stress to the induction of a novel cell death modality termed ferroptosis. However, the induction of this iron-regulated, caspase-independent cell death pathway has never been explored outside of the soma. Ferroptosis is initiated through the inactivation of the lipid repair enzyme glutathione peroxidase 4 (GPX4) and is exacerbated by the activity of arachidonate 15-lipoxygenase (ALOX15), a lipoxygenase enzyme that facilitates lipid degradation. Here, we demonstrate that male germ cells of the mouse exhibit hallmarks of ferroptosis including; a caspase-independent decline in viability following exposure to oxidative stress conditions induced by the electrophile 4-hydroxynonenal or the ferroptosis activators (erastin and RSL3), as well as a reciprocal upregulation of ALOX15 and down regulation of GPX4 protein expression. Moreover, the round spermatid developmental stage may be sensitized to ferroptosis via the action of acyl-CoA synthetase long-chain family member 4 (ACSL4), which modifies membrane lipid composition in a manner favourable to lipid peroxidation. This work provides a clear impetus to explore the contribution of ferroptosis to the demise of germline cells during periods of acute stress in in vivo models.